Comparative Theology Among Multiple Modernities: Cultivating Phenomenological Imagination - Chung, Paul S. (SpringerLink Bücher, 2017)
This book presents a heuristic and critical study of comparative theology in engagement with phenomenological methodology and sociological inquiry. It elucidates a postcolonial study of religion in the context of multiple modernities